Development of a phase-shifting interferometer for surface inspection - Low, Beng Yew. (2008)
This project aims at making full use of present day technology to implement a Digital Phase-Shifting Interferometer that can be used to determine the form errors of any reflective precision flat or curved surfaces. The computerised system takes over the laborious job of analysing the interferogram and provides a faster and more accurate acquisition of the interference images. The measurement accuracy and consistency are determined for various fringe processing technique. Uniform averaging, Gaussian weighted averaging, spin filtering and repetitive spin filtering are attempted. Finally, the flatness of three different surfaces - a cosmetic mirror, a test flat and silicon wafer were examined.